Effects of Food Insecurity on Health Conditions among Women and Children of Orang Asli Kintak in Pengkalan Hulu, Perak, Malaysia - Hasni, Nor Haidanadia; Halim, Sharina Abdul; Aziz, Sarah (Journal of Ecohumanism, 2024)
Growing evidences have shown high overlap between food, well-being and forest conservation. Such circumstances are being faced by indigenous communities, in Peninsular Malaysia that are becoming more vulnerable due to health problems related to malnutrition. In this paper, we address effects of food insecurity and health conditions among Orang Kintak mothers and children in Pengkalan Hulu. A total of 35 mothers and 63 children were sampled using quantitative approach. Using (WHO) reference standards, main finding for BMI classification of women shows (20%) underweight, (60%) normal weight and (20%) obesity. Meanwhile, (86%) children were under weight and only (14%) are of normal weight. Understanding the health problems faced by Orang Kintak following unbalanced and nutritional diet are crucial in order for local authorities and communities to take critical action, such as to set up a basic food source production program in order to avoid over dependent on purchased food sources. Next, increase the productivity of human capital by encouraging involvement in the economic, education and health sectors. In general, policy-makers need to take into account indigenous knowledge, challenges and beliefs system when making a strategic decision so that it is beneficial and suitable for the planned strategy to be successful.